Legal Aspect of Digital Transformation of Coffee and Tobacco Products in Batursari Village, Kledung Temanggung Indonesia - Maskur, Muhammad Azil; Fikri, Wildan Azkal; Indraswara, Dede (Universitas Negeri Semarang, 2024)
This study examines the legal aspects of the digital transformation of coffee and tobacco products in Batursari Village, Kledung, Temanggung, Indonesia, with a focus on enhancing the welfare of local entrepreneurs. Batursari Village, rich in natural resources, has significant potential for growth in its coffee and tobacco industries. The research aims to develop strategies for improving the welfare of these entrepreneurs through product digitalization, aligning with the mandate of Article 33 of the 1945 Constitution, which emphasizes the principle of kinship in the economy. Utilizing a mixed-methods approach, including surveys and focus group discussions with local entrepreneurs, the study identifies key challenges and opportunities in digital transformation. While the potential for expanding market access and increasing productivity through digital tools is evident, a lack of digital literacy and limited technological access have been significant barriers. The research highlights the importance of addressing legal aspects related to digital marketing, e-commerce regulations, and compliance with product standards. The study concludes that empowering local entrepreneurs with training in digital marketing and e-commerce can significantly improve market access, productivity, and overall welfare. Recommendations include implementing technical guidance sessions and providing ongoing support to facilitate the adoption of digital tools. Additionally, addressing legal and policy challenges is crucial to create a supportive environment for digitalization in rural economies. This research contributes valuable insights into how digital transformation can be harnessed to boost economic growth and welfare in rural agricultural communities, with a specific focus on Batursari Village’s coffee and tobacco industries.